American juvenile justice - Zimring, Franklin E. (New York ; Oxford : Oxford University Press, 2005)
Focusing on the priniples & policy of a separate & distinct system of juvenile justice, this text explores the criminology & policy analysis of adolescence.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Juvenile justice, Administration of -- United States; Juvenile delinquency -- Government policy -- United States; Juvenile courts -- United States